REASONING READINESS—THE VERY FIRST R: Semiotic Skills Engender Basic Skills - Chiasson, Phyllis (Signs - International Journal of Semiotics, 2008)
Embedded within the philosophy of Charles Sanders Peirce is a prescription for a semiotic skill development program to bring about reasoning readiness skills in students of all ages. The following article will explain how this semiotic skill development system connects with Peirce’s phenomenology and normative science. Following this theoretical discussion will be a brief discussion of each of the three basic semiotic skill sets: qualifying, analyzing, and representing/ interpreting signs. Each of these will explained and provided with suggestions for ways of engaging students with these skill sets.